Timing and Positioning of Simulated Hail Damage Effects on Wheat Yield in Kansas - R. Lollato; B. R. Jaenisch; R. Maeoka; A. de Oliveira Silva; C. Sciarresi (Kansas Agricultural Experiment Station Research Reports, 2017)
Hail events often decrease wheat yields in Kansas; however, estimates of yield loss due to hail event timing and position relative to the flag leaf are only available for old varieties. Our objectives were to quantify wheat yield losses as affected by timing of hail event relative to the crop development and positioning of the damage relative to the flag leaf. A total of 12 hail damage treatments including six different timings during the growing season (boot, anthesis, milk, soft dough, hard dough, and ripe) and two different positionings relative to the flag leaf (above or below) were evaluated in a trial conducted in Manhattan, KS, during the 2015-16 growing season. Hail damage was simulated by bending 100% of the stems within each plot. Wheat yield loss due to stem bending treatment ranged from 5.8 bushels per acre (9.0%) for treatment imposed below the flag leaf during hard dough to as much as 23.7 bushels per acre (36.7%) for treatment imposed during the milk stage, above the flag leaf. The greatest loss in wheat grain test weight was 4.5 pounds per bushel (8.1%) for treatments established during the milk stage. More years of research are needed to achieve robust estimates of wheat yield loss due to hail damage, but these preliminary data indicate that the milk stage of development is more sensitive to hail damage than other studied stages.